Species diversity and biting activity of Anopheles dirus and Anopheles baimaii (Diptera: Culicidae) in a malaria prone area of western Thailand - Tananchai, Chatchai (BioMed Central, 2012)
BACKGROUND: A survey of adult anopheline mosquito diversities, collected from September 2009 to August 2010, was conducted in a malaria endemic area of western Thailand. Two anopheline species complexes, Dirus and Minimus, along with the Maculatus group were observed. Of several species documented from within each complex and group, four important malaria vectors were identified, including An. dirus, An. baimaii, An. minimus, and An. sawadwongporni. Information on biting activity and host preference for any single species within the Dirus complex has never been assessed. Using specific molecular identification assays, the trophic behavior and biting activity of each sibling species within the Dirus complex were observed and analyzed for the Kanchanaburi Province, Thailand. METHODS: Adult female mosquitoes were collected for two consecutive nights each month during a one year period. Three collection methods, human landing indoor (HLI), human landing outdoor (HLO), and cattle baited collections (CBC) were applied. Each team of collectors captured mosquitoes between 1800 and 0600 h. RESULTS: From a total of 9,824 specimens, 656 belong to the Dirus complex (An. dirus 6.09% and An. baimaii 0.59%), 8,802 to the Minimus complex (An. minimus 4.95% and An. harrisoni 84.65%) and 366 to the Maculatus group (An. maculatus 2.43% and An. sawadwongporni 1.29%). Both An. dirus and An. baimaii demonstrated exophagic and zoophilic behaviors. Significantly greater numbers of An. dirus and An. baimaii were collected from cattle as compared to humans (P = 0.003 for An. dirus and P = 0.048 for An. baimaii). CONCLUSIONS: Significantly greater numbers of An. dirus and An. baimaii were collected from cattle baited traps as compared to human landing collections (P < 0.05), demonstrating that both species show a strong zoophilic behavior. Knowledge of host-seeking behavior helps to define a species' capacity to acquire and transmit malaria and its contribution to the overall risk for disease transmission in the human population, as well as, assisting in the design and implementation of appropriate vector prevention and control strategies.